Research methods and empirical evaluations of the influence of corporate culture on organizational effectiveness - Zhang xingang; Koshkina Olga (World Scientific Reports, 2024)
This essay addresses research methodologies and empirical evaluations of how corporate culture affects an organization's efficacy. In order to sustain the enterprise's competitiveness, boost employee engagement, and create a positive work environment, corporate culture is essential. The study's theoretical section examines current definitions, organizational frameworks, and techniques for evaluating corporate culture. Practically speaking, case studies, interviews, questionnaires, and content analysis are examples of how different research methodologies are used to determine the connection between an organization's corporate culture and its output. Applying an integrated strategy that blends quantitative and qualitative methodologies for a more thorough evaluation of the influence of company culture on performance metrics is what makes this research interesting. The study also suggests new empirical methods for examining corporate culture in businesses, which advances management theory and business practices in light of global shifts. The paper has theoretical significance because it advances our understanding of corporate culture's function in strategic management and how it affects an organization's long-term viability. The potential to use the suggested techniques and models to enhance corporate culture, boost worker productivity, and streamline business procedures in organizations is what gives the research its practical value